2013
DOI: 10.1007/s00251-013-0711-z
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms and tissue expression of the feline leukocyte antigen class I loci FLAI-E, FLAI-H, and FLAI-K

Abstract: Cytotoxic CD8+ T-cell immunosurveillance for intracellular pathogens, such as viruses, is controlled by classical major histocompatibility complex (MHC) class Ia molecules, and ideally, these antiviral T-cell populations are defined by the specific peptide and restricting MHC allele. Surprisingly, despite the utility of the cat in modeling human viral immunity, little is known about the Feline Leukocyte Antigen class I complex (FLAI). Only a few coding sequences with uncertain locus origin and expression patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 91 publications
0
21
0
Order By: Relevance
“…Sequencing of the FLA genomic region has revealed 19 FLA-I and 13 FLA-II loci within the 2.98 Mb genomic sequence of accession number EU153401 (Yuhki et al, 2008) (Figure 1). In comparison with the human MHC (human leukocyte antigen; HLA) genomic region, the FLA genomic region has the following features: (1) the 19 FLA-I loci are located in genomic regions corresponding to the HLA-B, HLA-C and HLA-E subregions, (2) three FLA-DRA and five FLA-DRB loci are located in the MHC-DR subregion, but the FLA-DRB5 locus, that is not found in DR haplotype 1, is located in the genomic sequence of another MHC-DR haplotype (DR haplotype 2 in Figure 1), (3) a similar gene organization was observed in the DM/DO subregion between both species, (4) no FLA loci are found in orthologous regions corresponding to the HLA-A, HLA-A/G/F, and HLA-DQ subregions, and (5) FLA-DPA1 and FLA-DPB1 loci are located in the orthologous HLA-DP subregion, but both of them are distinct pseudogenes (Yuhki and O'Brien, 1997;Beck et al, 2001;Yuhki et al, 2008;Holmes et al, 2013) (Figure 1).…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Sequencing of the FLA genomic region has revealed 19 FLA-I and 13 FLA-II loci within the 2.98 Mb genomic sequence of accession number EU153401 (Yuhki et al, 2008) (Figure 1). In comparison with the human MHC (human leukocyte antigen; HLA) genomic region, the FLA genomic region has the following features: (1) the 19 FLA-I loci are located in genomic regions corresponding to the HLA-B, HLA-C and HLA-E subregions, (2) three FLA-DRA and five FLA-DRB loci are located in the MHC-DR subregion, but the FLA-DRB5 locus, that is not found in DR haplotype 1, is located in the genomic sequence of another MHC-DR haplotype (DR haplotype 2 in Figure 1), (3) a similar gene organization was observed in the DM/DO subregion between both species, (4) no FLA loci are found in orthologous regions corresponding to the HLA-A, HLA-A/G/F, and HLA-DQ subregions, and (5) FLA-DPA1 and FLA-DPB1 loci are located in the orthologous HLA-DP subregion, but both of them are distinct pseudogenes (Yuhki and O'Brien, 1997;Beck et al, 2001;Yuhki et al, 2008;Holmes et al, 2013) (Figure 1).…”
Section: Introductionmentioning
confidence: 68%
“…Of the 19 classified FLA-I loci, three (FLA-E, FLA-H, and FLA-K) are classical, nine (FLA-A, FLA-C, FLA-F, FLA-J, FLA-L, FLA-M, FLA-O, FLA-Q, and FLA-S) are non-classical and the other seven loci are pseudogene fragments (Yuhki et al, 2008). The FLA-E, FLA-H, and FLA-K loci were characterized as classical class I genes (class Ia) by variability index plot analysis and detailed gene expression analyses (Holmes et al, 2013). However, for the other FLA loci, the gene expression and structural characteristics such as conservation of coding sequence (CDS) is unknown, although a mRNA sequence was identified that is highly similar to FLA-J (97.2% identity with EU915358).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FLA-E*01801 (previously known as FLA-B*n06) has been used to study the immune effect of the FIV vaccine (36). To illustrate the structural basis of FIV peptide presentation by FLA I, we solved the crystal structure of FLA-E*01801 in complex with a nonameric peptide derived from an FIV gag protein (RMA9 [RMANVSTGR]).…”
mentioning
confidence: 99%
“…c R ϭ ⌺ hkl || F obs | Ϫ k | Fcalc | |⌺ hkl | F obs |, where R free is calculated for a randomly chosen 5% of reflections and R work is calculated for the remaining 95% of reflections used for structure refinement. with the prospective model of polymorphic and conserved sites in the ␣1/␣2 domains (36). Three hypervariable regions (HVRs) were identified, namely, positions 62 to 81 in the ␣-helix of the ␣1 domain, positions 94 to 116 in the ␣-helix, and positions 94 to 116 in the ␤-strand of the ␣2 domain.…”
mentioning
confidence: 99%